2023
DOI: 10.1093/bjd/ljad028
|View full text |Cite
|
Sign up to set email alerts
|

The use of ultrasound and magnetic resonance imaging in the management of hidradenitis suppurativa: a narrative review

Abstract: Hidradenitis suppurativa (HS) is a chronic, inflammatory follicular skin disease that frequently affects the apocrine gland-bearing skin of the axillary, inguinal and anogenital regions. HS has a significant impact on the psychosocial health and quality of life of patients. Diagnosis of HS is typically clinical, and reliant on the ability of physicians to recognize the signs of HS. However, lesions may present at the dermal and subcutaneous skin layers, which cannot be diagnosed by clinical examination alone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The use of US, particularly UHFUS examination, has demonstrated its potential to revolutionize the field of dermatology by providing valuable insights into the development of an objective and standardized staging method for various skin disorders [31][32][33][34]. In this context, our study represents the first experience with UHFUS in patients affected by PG lesions presented in the literature.…”
Section: Discussionmentioning
confidence: 89%
“…The use of US, particularly UHFUS examination, has demonstrated its potential to revolutionize the field of dermatology by providing valuable insights into the development of an objective and standardized staging method for various skin disorders [31][32][33][34]. In this context, our study represents the first experience with UHFUS in patients affected by PG lesions presented in the literature.…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, there is a need to reduce diagnostic delays by supporting accurate and early recognition of HS to limit disease progression and manage the comorbidity burden ( 14 , 16 ). Some studies have reported the use of ultrasound (US) imaging as a characterizing diagnostic tool in conjunction with clinical examination to reduce the uncertainty of HS diagnosis and inform on optimal therapeutic strategies, primarily by detecting inflammatory activity and the early subclinical and dermal features of HS and accurately characterizing lesion morphology ( 17 19 ). The use of US for diagnosis is a promising approach to both diagnosis and staging; however, its application in the practice setting is limited at present because it has not yet been standardized or validated.…”
Section: Introductionmentioning
confidence: 99%
“…In oncology, it aids in early diagnosis, provides critical information about tumor depth, locoregional staging, prognosis, surgical planning and postoperative assessment of treatment outcomes (4). Within clinical Dermatology, US finds utility in the diagnosis of benign tumors, characterizing nail pathology, differentiating autoimmune bullous diseases and monitoring inflammatory conditions such as psoriasis, atopic dermatitis, morphea and hidradenitis suppurativa (5)(6)(7). In aesthetic medicine, the US serves as a valuable tool for guiding filler injections, managing complications, and tracking treatment outcomes (3,8).…”
Section: Introductionmentioning
confidence: 99%